PERAN MAHASISWA MAGANG DALAM OPTIMALISASI TATA KELOLA ADMINISTRASI KEMENTERIAN AGAMA KABUPATEN GOWA - Nensilianti; Alifia Aprilyta , Fitri; muwinda , Rahma; Nurul Magfirah Syam, Nisa; Subriyana (MEDIA INOVASI PENDIDIKAN DAN PUBLIKASI, 2025)
The independent internship program at the Ministry of Religious Affairs Office of Gowa Regency was implemented to address administrative challenges that remained manual, unstructured, and constrained by limited human resources in data management, archiving, and correspondence services. This program aims to optimize administrative governance while enhancing students’ professional competencies through direct involvement in bureaucratic workflows. The methods employed included observation, field-based technical practice, limited interviews and documentation. The results show that the students successfully input 178 Monthly Performance Report (LKB) documents, updated 64 employee records, organized 214 personnel files, validated 132 performance allowance data entries, and assisted in preparing monthly financial reports with 95% accuracy. Additionally, the students updated 76 institutional profiles in the EMIS system, verified 54 waqf documents, and recorded 286 civil servants eligible for professional zakat contributions. The program significantly improved administrative efficiency, strengthened data accuracy, and accelerated service delivery across all divisions. Furthermore, students experienced notable improvements in their technical skills, digital literacy, professional communication, and workplace discipline. Thus, this program effectively supports the modernization of administrative services while preparing students to become competent, work-ready professionals.